1982
DOI: 10.1007/bf01283163
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response inHeterodontus

Abstract: Appropriately selected phylogenetic models are capable of providing insight into genetic mechanisms which may have become obscured during the passage of evolutionary time. In higher vertebrates a complex multigenic family encodes immunoglobulin-variable regions. The mechanisms involved in the expansion of the gene family and the stable maintenance of large numbers of individual genes presently are not understood. By defining the nature of antibody diversity in lower vertebrate species, it may be possible to ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…It has been suggested that germline responses predominate in poikilothermic vertebrates, since slower cell cycle rates and pressure for expression of pathogen-specific antibody during ex utero ontogenetic development would make somatic mutation-selection temporally inefficient (33). The immune response characteristics of Heterodontus and another elasmobranch are consistent with this hypothesis as there is no apparent change in antibody fine specificity (11)(12)(13) and affinity (11)(12)(13)34) over prolonged periods of immunization.…”
Section: ----------------------------------------------------------'>mentioning
confidence: 90%
See 3 more Smart Citations
“…It has been suggested that germline responses predominate in poikilothermic vertebrates, since slower cell cycle rates and pressure for expression of pathogen-specific antibody during ex utero ontogenetic development would make somatic mutation-selection temporally inefficient (33). The immune response characteristics of Heterodontus and another elasmobranch are consistent with this hypothesis as there is no apparent change in antibody fine specificity (11)(12)(13) and affinity (11)(12)(13)34) over prolonged periods of immunization.…”
Section: ----------------------------------------------------------'>mentioning
confidence: 90%
“…T which inversely complements the gene sequence of a Heterodontus heavy chain constant region peptide, Trp-Lys-LysGly-Glu-Glu (11), and a 24-mer,…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, upon secondary antigenic challenge, horned sharks do not show a dramatic rise in levels of antibody. Rather, the increase requires repeated monthly immunizations and occurs over a much longer time interval than is seen in mammals (108,109).…”
Section: B Cell Memory and The Secondary Immune Responsementioning
confidence: 99%